Comparative Evaluation of Modified Canal Staining and Clearing Technique, Cone-Beam Computed Tomography, Peripheral Quantitative Computed Tomography, Spiral Computed Tomography, and Plain and Contrast Medium–enhanced Digital Radiography in Studying Root Canal Morphology - Neelakantan, Prasanna; Subbarao, Chandana; Subbarao, Chandragiri V. (Journal of endodontics, 2010)
This study investigated the accuracy of cone-beam computed tomography (CBCT), peripheral quantitative computed tomography (pQCT), spiral computed tomography (SCT), plain (plain digi), and contrast medium–enhanced digital radiographs (contrast digi) in studying root canal morphology. The root canal anatomy was analyzed in 95 teeth using CBCT, pQCT, SCT, plain digi, and contrast digi. After flushing out the radiopaque dye, access cavities were sealed, and the teeth were subject to the modified canal staining and clearing technique. The number of root canals (Vertucci classification and Gulabivala's additional classes) was calculated by three calibrated endodontists and two maxillofacial radiologists. Erroneous or unsuccessful identifications of root canals were statistically analyzed by one-way analysis of variance (p = 0.05). The modified canal staining and clearing technique identified an average of 1.8 root canals per mandibular central incisor, 2.3 per maxillary first premolar, 3.9 per maxillary first molar, 3.8 per maxillary and mandibular second molar, and 4.3 per mandibular first molar. CBCT and pQCT were erroneous in 0.29% and 2.05% cases, whereas SCT, contrast digi, and plain digi were unsuccessful in 15.58%, 14.7%, and 23.8%, respectively. There was a significant difference between all the methods (p < 0.05) in the unsuccessful identification of root canals except between CBCT and modified canal staining and clearing technique where there was no significant difference (p > 0.05). CBCT and pQCT were as accurate as the modified canal staining and tooth clearing technique in identifying root canal systems.